2005
DOI: 10.1007/s10809-005-0256-x
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the Insecticide Imidacloprid in Potato (Solanum tuberosum L.) and Onion (Allium cepa) by High-Performance Liquid Chromatography with Diode-Array Detection

Abstract: A high-performance liquid chromatography (HPLC) method has been proposed for the determination of imidacloprid residues in fortified potato ( Solanum tuberosum L.) and onion ( Allium cepa ) and in treated potato and onion samples. Sample preparation consisted of dichloromethane extraction of imidacloprid from the plant material, followed by purification of the obtained onion extract on an LC-Florisil disposable cartridge. The obtained potato extracts were further analyzed without purification. The HPLC-diode-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 19 publications
(22 reference statements)
1
22
1
Order By: Relevance
“…A mixture of water and acetonitrile is commonly used for the HPLC separation of different neonicotinoids on a reverse phase (Mandić et al 2005;Rancan et al 2006). In the procedure of mobile phase optimization it was found that the increase of acetonitrile content, e.g.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A mixture of water and acetonitrile is commonly used for the HPLC separation of different neonicotinoids on a reverse phase (Mandić et al 2005;Rancan et al 2006). In the procedure of mobile phase optimization it was found that the increase of acetonitrile content, e.g.…”
Section: Resultsmentioning
confidence: 99%
“…However, because of the thermolability and low volatility of neonicotinoids, the GC/MS procedures involve complex sample preparation. Hence, liquid chromatographic methods such as HPLC/DAD (Obana et al 2002;Mandić et al 2005), HPLC/MS (Obana et al 2003;Fidente et al 2005;Seccia et al 2005), and HPLC/post-column photoactivation/electrochemical detection (Rancan et al 2006) appeared to be advantageous for the determination of neonicotinoids in various matrices.…”
Section: Introductionmentioning
confidence: 99%
“…However, GC determination can produce overestimated values of highly polar compounds such as acetamiprid because of the matrix-induced enhancement effect (Sasaki et al, 1998). For determination of other neonicotionoids, such as imidacloprid, the highperformance liquid chromatography is already commonly used (Mandić et al, 2005). In this study, acetamiprid was determined by HPLC.…”
Section: Methods Validationmentioning
confidence: 99%
“…Ferrer, I., Thurman, E.M. and Fernandez-Alba, A.R. : Quantitation and accurate mass analysis of pesticides in vegetables by LC/TOF-MS. Analytical Chemistry, 77: 2818-2825, 2005 Analysis of nicotinoid insecticides residues in honey by solid matrix partition clean-up and liquid chromatography-electrospray mass spectrometry. Journal of Chromatography A, 1094: 175-178, 2005.…”
Section: Measurement Uncertaintymentioning
confidence: 99%
“…For this reason, the concentration of neonicotinoid residues, including their metabolites, in agricultural products should be monitored. This requires appropriate methods of extraction and determination, such as the already existing methods for imidacloprid in potato and onion (Mandić et al, 2002(Mandić et al, , 2005Lazić et al, 2002Lazić et al, , 2003Lazić et al, , 2004, or thiamethoxam in pepper (Lazić et al, 2002a).…”
Section: Introductionmentioning
confidence: 99%